Strain-enhanced phase transformation of iron oxide for higher alcohol production from CO2 - Goud, Devender; Churipard, Sathyapal R.; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Vinod, C. P.; Peter, Sebastian C. (ACS Catalysis, 2022)
Conversion of CO2 to higher alcohols (HAs) and higher hydrocarbons (HCs) has a greater advantage compared to C1 products because of their high energy density and wide range of applications in daily life. Despite the immense potential of these chemicals, not much of scientific research has been focused on the conversion of CO2 to HAs. In the present work, we have introduced the concept of strain in designing the material to enhance the CO(2 )to HA performance. We introduced strain in a traditional iron-based catalyst, Fe2O3, by the introduction of indium (In), which facilitates the selective conversion of CO2 to HA. An optimum strain favored a 36.7% CO2 conversion with a 42% HA selectivity, and a record yield of 15.42%. The strain has been tuned further with the introduction of K as a promoter. The introduced strain upon In substitution and K promotion favored the conversion of CO2, which is mapped by powder X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy. Further, the change in the mechanism upon In incorporation and K promotion has been probed by in situ diffuse reflectance infrared fourier transform spectroscopy, and it is found that the OCHx intermediate, which produces HAs, is more prominent upon In substitution, which favored the enhancement of HA production compared to that of pristine Fe2O3.
Keywords: CO2 to HA; Fischer-Tropsch synthesis (FTS); Phase transformation; reverse water gas shift (RWGS) reaction; strain

Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.

Distortion-induced interfacial charge transfer at single cobalt atom secured on ordered intermetallic surface enhances pure oxygen production - Mondal, Soumi; Riyaz, Mohd; Bagchi, Debabrata; Dutta, Nilutpal; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2023)
In this work, atomic cobalt (Co) incorporation into the Pd2Ge intermetallic lattice facilitates operando generation of a thin layer of CoO over Co-substituted Pd2Ge, with Co in the CoO surface layer functioning as single metal sites. Hence the catalyst has been titled Co-1-CoO-Pd2Ge. High-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy confirm the existence of CoO, with some of the Co bonded to Ge by substitution of Pd sites in the Pd2Ge lattice. The role of the CoO layer in the oxygen evolution reaction (OER) has been verified by its selective removal using argon sputtering and conducting the OER on the etched catalyst. In situ X-ray absorption near-edge structure and extended X-ray absorption fine structure spectroscopy demonstrate that CoO gets transformed to CoOOH (Co3+) in operando condition with faster charge transfer through Pd atoms in the core Pd2Ge lattice. In situ Raman spectroscopy depicts the emergence of a CoOOH phase on applying potential and shows that the phase is stable with increasing potential and time without getting converted to CoO2. Density functional theory calculations indicate that the Pd2Ge lattice induces distortion in the CoO phase and generates unpaired spins in a nonmagnetic CoOOH system resulting in an increase in the OER activity and durability. The existence of spin density even after electrocatalysis is verified from electron paramagnetic resonance spectroscopy. We have thus successfully synthesized intermetallic supported CoO during synthesis and rigorously verified the role played by an intermetallic Pd2Ge core in enhancing charge transfer, generating spin density, improving electrochemical durability, and imparting mechanical stability to a thin CoOOH overlayer. Differential electrochemical mass spectrometry has been explored to visualize the instantaneous generation of oxygen gas during the onset of the reaction.
Keywords: DEMS; interfacial charge transfer; Intermetallic; long-termstability; operando spectroscopic techniques; Oxygen Evolution Reaction; structuraldistortion

Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis

Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis

Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis